Systematic review of professional development of teachers of multilingual learners in the mathematics classroom - Gift Onwubuya (Social Sciences and Humanities Open)
Recent scholarship on multilingual learners (MLs) often highlights classroom marginalization and linguistic discourse, yet there is limited focus on pedagogical strategies and professional development (PD) for ML teachers. This article reviews mathematics education literature from 2009 to 2023, focusing on K–12 ML teacher PD. The study identifies three key activity systems: language pedagogy-based approaches, teaching beliefs and competencies, and integration of content and language PD. These systems enhance teachers' ability to support MLs' academic engagement and sociolinguistic inclusion. The findings point to the importance of PD that embraces linguistic diversity and equips teachers to foster inclusive, equitable mathematics learning environments.